2019
DOI: 10.1105/tpc.19.00275
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor Activity Contributes to Contrasting Responses to Shade in Cardamine and Arabidopsis Seedlings

Abstract: Plants have evolved two major ways to deal with nearby vegetation or shade: avoidance and tolerance. Moreover, some plants respond to shade in different ways; for example, Arabidopsis thaliana undergoes an avoidance response to shade produced by vegetation, but its close relative Cardamine hirsuta tolerates shade. How plants adopt opposite strategies to respond to the same environmental challenge is unknown. Here, using a genetic strategy, we identified the C. hirsuta slender in shade1 (sis1) mutants, which pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(79 citation statements)
references
References 66 publications
2
76
1
Order By: Relevance
“…scant elongation under low light), the plasticity of some characteristics, especially the morphological characteristics of optimizing light capture, can be high in these plants (Smith, 1982;Valladares and Niinemets, 2008). Cardamine hirsuta is a close relative of Arabidopsis thaliana, and it is suggested that the lack of a shade-induced hypocotyl elongation response in C. hirsuta results from the enhanced repressor activity of the phytochrome A photoreceptor (Molina-Contreras et al, 2019). Exploitation of the molecular basis of shade-avoidance and shade-tolerance to improve crop yield and quality is of considerable importance for highdensity cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…scant elongation under low light), the plasticity of some characteristics, especially the morphological characteristics of optimizing light capture, can be high in these plants (Smith, 1982;Valladares and Niinemets, 2008). Cardamine hirsuta is a close relative of Arabidopsis thaliana, and it is suggested that the lack of a shade-induced hypocotyl elongation response in C. hirsuta results from the enhanced repressor activity of the phytochrome A photoreceptor (Molina-Contreras et al, 2019). Exploitation of the molecular basis of shade-avoidance and shade-tolerance to improve crop yield and quality is of considerable importance for highdensity cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…and XTR7, known to be direct PIF target genes in A. thaliana, was strongly and rapidly enhanced in chfr1 and RNAi-HFR1 seedlings (Figure 1c, d). More importantly, rapid shade-induced expression was globally attenuated in Ch WT compared to At WT seedlings 26 .…”
Section: Discussionmentioning
confidence: 95%
“…In particular, the identification and characterization of the C. hirsuta phyA-deficient slender in shade 1 (sis1) mutant indicated that differential features of this photoreceptor in A. thaliana and C. hirsuta could explain their differential response to shade. Thus, stronger phyA activity in C. hirsuta wild-type plants resulted in a suppressed hypocotyl elongation response when exposed to low or very low R:FR 26 . These approaches indicated that the implementation of shade avoidance and shade tolerance involved the participation of shared genetic components.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations